Single-beam phase shift tracker with continuous musical palpations for mobile elastography - Chang, Seoyun; Yu, Hwanseung; Park, Jinhyoung (Journal of sound and vibration, 2021)
The maintenance and monitoring of skin health have been an issue of concern for a long time. While many technologies for daily skin monitoring have been proposed, these methods only have the capability to inspect superficial skin layers. Ultrasonic elastography has been used for measuring the stiffness of deeper soft tissue, however, the current technologies are not compatible with the mobile environment. In this paper, we present a solution for quantitative ultrasonic elastography compatible with mobile environments utilizing ubiquitous sound sources, such as voices of the users or music played by a smartphone for remotely palpating the deep skin layer. In addition, instead of using an array ultrasound, the proposed technology only requires a single-element transducer to perform repetitive ultrasonic transmissions and receptions of the tracking echo signals. The proposed algorithm could successfully quantify the stiffness of tissue phantoms and skin regions in human subjects. The performance of the proposed elastography was comparable with that of a commercial system. Owing to the reduction in hardware requirements, single-beam tracking elastography could be integrated into current mobile devices.